Respuesta :

Answer:

D.  4

Step-by-step explanation:

Given expression:

[tex]-2x^2-4x+10[/tex]

To find the value of the expression when x = -3, substitute x = -3 into the expression:

[tex]\implies -2(-3)^2-(-3)x+10[/tex]

Apply exponent rule  [tex](-a)^2=a^2[/tex]:

[tex]\implies -2(3^2)-4(-3)+10[/tex]

[tex]\implies -2(9)-4(-3)+10[/tex]

[tex]\implies -18-4(-3)+10[/tex]

Apply rule [tex]-(-a)=a[/tex] :

[tex]\implies -18+(4)(3)+10[/tex]

[tex]\implies -18+12+10[/tex]

Add/subtract from left to right:

[tex]\implies -6+10[/tex]

[tex]\implies 4[/tex]

Let's find

  • -2x²-4x+10
  • -2(-3)²-4(-3)+10
  • -2(9)+12+10
  • -18+22
  • 4

Otras preguntas